Multi-mineral geochronology: insights into crustal behaviour during exhumation of an orogenic root - LaFlamme, C.; McFarlane, C.; Fisher, C.; Kirkland, Chris (Springer, 2017)
Under rare conditions, reworked cratons and their margins preserve the orogenic roots of ancient mountain-building events. However, based on the preservation of high-temperature (~ 800 °C), middle and lower crustal metamorphic assemblages, present day exposure of these terrains is not simply a result of protracted denudation, but also must reflect a multifaceted exhumational history. In situ analysis within thin section preserves the textural setting of target minerals that can be used as thermochronometers such as U-Pb of zircon, monazite, titanite and apatite, and Sm-Nd of apatite. In situ analyses of these chronometers has the potential to provide critical timing constraints on exhumation processes related to decompression, melting and cooling across large metamorphic terrains. The Repulse Bay block of the Rae craton preserves a large composite amphibolite–granulite area (50,000 km2) of Archean orthogneiss, migmatite, and slivers of Proterozoic metasediments that underwent high-grade metamorphism, partial melting, ductile flow and finally exhumation during the Paleoproterozoic Trans-Hudson Orogeny. The granulite domain preserves dry granitoid assemblages, whereas the amphibolite domain is dominated by hydrated migmatites and orthogneiss. Metasediments occur in both domains and preserve mineral assemblages that are consistent with having undergone tectonometamorphic conditions of ~ 9 kbar/800 °C during burial. U-Pb thermochronometers document identical cooling histories of the granulite and amphibolite domains through the U-Pb closure temperatures of titanite (~ 650 °C) and apatite (~ 450 °C). This suggests that melt-loss from the underlying granulite domain and melt-gain to the amphibolite domain prior to cooling through 650 °C are a controlling factor of the metamorphic assemblages across the composite granulite–amphibolite terrains such as the Repulse Bay block, rather than significant differences in burial history, cooling history, and/or reorganization of the crust.